Whole Child Education in the Context of Islamic Schools in the United States: Principals’ Perspectives - Brifkani, Isra (Religious education, 2021)
In light of calls for renewal in Islamic schooling in the West, this study reconceptualizes the notion that Islamic education promotes wholeness through tarbiyah. The author conducted interviews with twenty principals of Islamic schools in the United States to understand these principals’ perspectives regarding wholeness in education. The findings suggest that the principals strive for wholeness in education but may not be unified in understanding the components and implementation of whole child education from an Islamic perspective. An Islamic whole child education framework needs to be developed that encompasses the comprehensiveness and wholeness of tarbiyah as a framework for renewal.